Diagnosis of Faulty Sensors in Antenna Array using Hybrid Differential Evolution based Compressed Sensing Technique - Shafqat Ullah Khan; M. K. A. Rahim; I. M. Qureshi; N. A. Murad (Institute of Advanced Engineering and Science, 2017)
In this work, differential evolution based compressive sensing technique for detection of faulty sensors in linear arrays has been presented. This algorithm starts from taking the linear measurements of the power pattern generated by the array under test. The difference between the collected compressive measurements and measured healthy array field pattern is minimized using a hybrid differential evolution (DE). In the proposed method, the slow convergence of DE based compressed sensing technique is accelerated with the help of parallel coordinate decent algorithm (PCD). The combination of DE with PCD makes the minimization faster and precise. Simulation results validate the performance to detect faulty sensors from a small number of measurements.